Stakeholder Perceptions as Strategic Communication Strategy in the Management of Forest Park Conservation in Riau - M. Rafi; Al Fauzi Rahmat; Hazqon Fuadi Nasution; Rico Purnawandi Pane; Agus Susanto (Universitas Muhammadiyah Yogyakarta, 2024)
This research aims to analyze the prevailing conditions and determinants shaping individuals' perceptions concerning the management practices of the Great Forest Park conservation area within Riau Province. Employing a qualitative research methodology, this study utilizes Nvivo 12 Plus software as a tool for data collection. The findings underscore that the management of the Great Forest Park conservation area in Riau Province is appraised through the lenses of preserving its protected function, institutional arrangements, collection preservation, recovery preservation, and sustaining utilization functions. However, significant enhancements are deemed requisite across each of these principles to foster improved management of the Grand Forest Park in Riau Province. Furthermore, various factors influencing public perceptions regarding the management of the Great Forest Park conservation area in Riau Province predominantly include the intensity of socialization endeavors, comprehension of the benefits derived from forest functions, community engagement in forest management initiatives, and participation in conservation-focused training programs.